FexNi9−xS8 (x = 3–6) as potential photocatalysts for solar-driven hydrogen production?. (3rd April 2019) - Tetzlaff, David; Simon, Christopher; Achilleos, Demetra S.; Smialkowski, Mathias; junge Puring, Kai; Bloesser, André; Piontek, Stefan; Kasap, Hatice; Siegmund, Daniel; Reisner, Erwin; Marschall, Roland; Apfel, Ulf-Peter
Abstract : The photocatalytic proton reduction is catalyzed by Fe x Ni x −9 S8 . Abstract : The efficient reduction of protons by non-noble metals under mild conditions is a challenge for our modern society. Nature utilises hydrogenases, enzymatic machineries that comprise iron- and nickel- containing active sites, to perform the conversion of protons to hydrogen. We herein report a straightforward synthetic pathway towards well-defined particles of the bio-inspired material Fe x Ni9− x S8, a structural and functional analogue of hydrogenase metal sulfur clusters. Moreover, the potential of pentlandites to serve as photocatalysts for solar-driven H2 -production is assessed for the first time. The Fe x Ni9− x S8 materials are visible light responsive (band gaps between 2.02 and 2.49 eV, depending on the pentlandite's Fe : Ni content) and display a conduction band energy close to the thermodynamic potential for proton reduction. Despite the limited driving force, a modest activity for photocatalytic H2 has been observed. Our observations show the potential for the future development of pentlandites as photocatalysts. This work provides a basis to explore powerful synergies between biomimetic chemistry and material design to unlock novel applications in solar energy conversion.